A commentary on the book of the twelve the minor prophets - Shepherd, Michael B. 1977- (Grand Rapids. MI Kregel Publications, 2018)
The books of the twelve Minor Prophets are some of the least studied by Christians today, but they contain some of the great themes of Scripture, such as God's mercy and judgment, His covenant with Israel, the day of the Lord, and the coming of the Messiah. Arguing for a canonical unity that recognizes the Minor Prophets as one cohesive composition, Michael Shepherd explains the historical meaning of each verse of the twelve books and also provides guidance for application and preaching. Pastors, teachers, and serious students of Scripture will find a wealth of insights for understanding the Minor Prophets. - from publisher
Hosea -- Joel -- Amos -- Obadiah -- Jonah -- Micah -- Nahum -- Habakkuk -- Zephaniah -- Haggai -- Zechariah -- Malachi.
Includes bibliographical references (pages 513-523)
Keywords: Bible -- Commentaries; Bible; Commentaries